Post-Activation Potentiation and Fatigue of Quadriceps Muscle after Continuous Isometric Contractions at Maximal and Submaximal Intensities - Nerijus Masiulis; Albertas Skurvydas; Sigitas Kamandulis; Jūratė Kudirkaitė; Vytautas Sukockas; Edmundas Valys; Vilma Jurevičienė; Lina Kamandulienė (Lithuanian Sports University, 2018)
The dominance of fatigue or post-activation potentiation (PAP) depends on the type, intensity, and duration of exercise and duration of the recovery before contractility is tested. Although the decrease in PAP magnitude with decreased exercise intensity is well documented (Vandervoort et al., 1983; Behm et al., 2004), it is not clear how PAP and fatigue influences the contractile properties of skeletal muscle when exercise is of different intensity but with the same amount of work performed. Thus it is important to understand the manifestation of PAP and fatigue of skeletal muscle after continuous maximal and submaximal contractions but with the same amount of work performed. Eight healthy untrained men (age 23-27 years, mass 83.5 ± 5.4 kg) performed maximal sustained isometric knee extension for 30 s (MVC-30 s) and on the other occasion the same subject performed sustained isometric knee extension for 60 s at 50% of maximal (50% MVC-60 s). We assumed that the amount of performed work was the same during both MVC-30 s and 50% MVC-60 s exercises. The experimental order was randomized. The contractile properties of quadriceps muscle evoked by electrical stimulation at 1 Hz (P 1), 10 Hz (P 10), 20 Hz (P 20), and 50 Hz (P 50) as well as contraction time (CT) and relaxation time (RT) of single twitch (P 1) and EMGrms of v. lateralis muscle were recorded before and immediately after the exercises (0 min) and 1, 2, and 3 min following the exercises. A significantly greater potentiation (p < 0.05) of P1 was observed after 30-s MVC (MVC-30 s) compared with the 60-s MVC (50% MVC-60 s) immediately after exercise and at 1 min of recovery. No changes in P 1 contraction time (CT) were observed during 3 min recovery period, however half relaxation of P 1 (½ RT) was more prolonged (p < 0.05) immediately after 50% MVC-60 s exercises. Moreover, immediately and 1 min post exercise the P 10 force after MVC-30 s exercise was higher (p < 0.05) compared to 50% MVC-60 s exercise. No differences between MVC-30 s and 50% MVC-60 s exercises were observed at high stimulation frequencies, maximal voluntary contraction force (MVC) as well as for EMGrms values during 3 min recovery period. The main finding of the present study was that PAP was observed after both maximal and submaximal intensity exercises when the same amount of work was performed. The more intensively exercise is performed, the more PAP offsets fatigue straight after exercise (maximal intensity); while after submaximal exercise PAP becomes more evident only during the recovery period. Keywords: skeletal muscle, isometric exercise, maximum voluntary contraction, recovery.